Facile synthesis of fluorescent carbon nanodots from starch nanoparticles - Suk, Fun Chin; Siti Nur Akmar, Binti Mohd Yazid; Suh, Cem Pang; Sing, Muk Ng (Elsevier B.V, 2012)
Fluorescent carbon dots were synthesized by the carbonization of preformed native sago starch nanoparticles, followed by surface oxidation in an aqueous medium. The morphology and particle sizes of carbon nanodots (CDs) were observed to be very similar to starch nanoparticles that were used as precursors. The particle sizes of CDs synthesized in this study were within the range 50–80 nm, which were much larger than those of very tiny CDs (1–5 nm) previously reported. The CDs portrayed fluorescent with constant emission wavelength peak at 430 nm when excited with various higher energy photons. The non-shifting of the emission wavelength peak suggested that CDs prepared in this study were highly homogenous and possessed mono-dispersed physiochemical properties.